2015
DOI: 10.1063/1.4930201
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid characterization of microscopic two-level systems using Landau-Zener transitions in a superconducting qubit

Abstract: We demonstrate a fast method to detect microscopic two-level systems in a superconducting phase qubit. By monitoring the population leak after sweeping the qubit bias flux, we are able to measure the two-level systems that are coupled with the qubit. Compared with the traditional method that detects two-level systems by energy spectroscopy, our method is faster and more sensitive. This method supplies a useful tool to investigate two-level systems in solid-state qubits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…* Micrometer-size superconducting qubits allow the realization of macroscopically distinct quantum states. The nonadiabatic transitions between them were demonstrated for a variety of JJ-based qubits, namely flux (Izmalkov et al, 2004), quantronium (Ithier et al, 2005), charge (Cooper pair sluice) (Gasparinetti et al, 2012), and phase (Tan et al, 2015) qubits. In these works, it was demonstrated that such measurements are useful for probing and controlling both the qubits themselves and the coupled microscopic systems, hence providing a fast and sensitive tool.…”
Section: Some Experimental Observationsmentioning
confidence: 99%
“…* Micrometer-size superconducting qubits allow the realization of macroscopically distinct quantum states. The nonadiabatic transitions between them were demonstrated for a variety of JJ-based qubits, namely flux (Izmalkov et al, 2004), quantronium (Ithier et al, 2005), charge (Cooper pair sluice) (Gasparinetti et al, 2012), and phase (Tan et al, 2015) qubits. In these works, it was demonstrated that such measurements are useful for probing and controlling both the qubits themselves and the coupled microscopic systems, hence providing a fast and sensitive tool.…”
Section: Some Experimental Observationsmentioning
confidence: 99%
“…where ω max /2π = 5423.5 MHz, ω c /2π = 23.7 MHz, d = −0.2447, M = 2.062, and V 0 = −0.0043 V, respectively. Due to the large junction area (≈1 µm 2 ), previous experiments have revealed characteristic level avoidance or anti-crossing on superconducting phase qubits [18][19][20][21][22], flux qubits [23,24], and Quantronium [25]. However, the junction area of the Xmon qubit used in this experiment is ≈200 nm 2 , and the spectroscopy in Figure 1b shows no obvious anti-crossing.…”
Section: Device and Methodsmentioning
confidence: 59%
“…TLS defects have been investigated using different methods based on superconducting qubits, such as direct microwave spectroscopy [18][19][20][21][22][23][24][25], strain spectroscopy [26][27][28], longterm time-domain measurement [29][30][31][32][33][34], dielectric loss and participation ratio [35][36][37]. These works partially analyze spectral or temporal data, or demonstrate with fixed-frequency qubits.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting quantum bits (qubits) [1] play a central role in superconducting quantum circuits, which are a promising candidate for solid-state quantum computing [2] and can serve as an excellent platform for the studies of quantum optics [3] and quantum simulation. [4] In addition to the various types of qubits such as charge, flux, and transmon (or Xmon), [1] the superconducting phase qubits [5][6][7][8][9][10][11][12][13][14][15][16][17] have been received much attention in the past years due to their unique properties and advantages. It is known that the phase qubit has a widely tunable anharmonicity α ranging from 0.1% to 10%, and it is convenient to couple the qubits capacitively or inductively, leading to the rich Hamiltonians that are desirable for developing circuit architectures for quantum simulators.…”
Section: Introductionmentioning
confidence: 99%